Sudden Blindness as Post-Hemodialysis Complication Experienced by Patients at The End-Stage of Kidney Disease: a Case Report - Perdhana, Langgeng; Chasani, Shofa; Martiningsih, Wahju Ratna; Yekti, Murwani; Arinawati, Arinawati (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: Hemodialysis is the most preferred Renal Replacement Therapy (RRT) options for End-Stage Kidney Disease (ESKD) patients. Although it is safe and beneficial for patients, several complications may occur during hemodialysis process. One complication that is rarely found in the hemodialysis process is visual impairment. Visual impairment or even sudden blindness occured during or within 24 hours post hemodialysis. Objective: To describe the occurring sudden blindness as a rare complication in patients undergoing hemodialysis and its etiology.Brief Case: 19 years old man with ESKD undergoing hemodialysis for 1 month with a complaint of sudden blindness in both eyes occurring <24 hours post hemodialysis.Discussion: Fast and precise efforts are needed to diagnose the etiology of blindness, so that prevention and appropriate treatment can be immediately taken. Multidisciplinary teamwork is needed to diagnose the etiology of visual impairment.Conclusion: Sudden blindness in this case may be caused by the 3rd degree hypertensive retinopathy caused by malignant hypertension and Posterior Reversible Encephalopathy Syndrome (PRES)